Preparation method and application of fine-grained sulfur-free expandable graphite

Through the electrochemical reaction preparation method of fine-grained scale graphite and sulfur-free intercalation agent, the existing expansionary graphite preparation methods are solved, and sulfur-free and low-cost expansionary graphite is prepared. The removal rate of fluoride ions is improved through composite materials.

CN119461361APending Publication Date: 2025-02-18HEILONGJIANG NUOKANG GRAPHITE NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411663113.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing expansionary graphite preparation methods have problems such as high cost, high sulfur content, and poor oxidation resistance, which limit their application and promotion.

Method used

Using fine-grained scale graphite, sulfur-free intercalation agent and electrochemical reactor, the sulfur-free, low-cost expandable graphite with different expansion volumes is prepared by controlling the current density and oxidation reaction time, and used to prepare expanded graphite-based Nickel-Vanadium bimetallic hydroxide composite material.

Benefits of technology

The sulfur-free and low-cost expansion graphite preparation is achieved, which meets the requirements for the quality of expandable graphite in different fields, and the removal rate of fluoride ions is improved through composite materials, reaching 96.8%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method and application of fine-grain sulfur-free expandable graphite, and relates to a preparation method and application of expandable graphite. Fine crystalline flake graphite powder is used as a raw material, a sulfur-free intercalator, namely a mixed solution of perchloric acid and anhydrous acetic acid, is adopted, the position of an electrode plate is fixed by utilizing an electrochemical reactor, and the current density and the oxidation reaction time are adjusted, so that the sulfur-free and low-cost expandable graphite with different expansion volumes is prepared; the current intensity can be increased by controlling the current density, and the oxidation intensity is controlled; the intercalation time can be controlled by adjusting the reaction time, and expandable graphite with different expansion volumes can be obtained; the removal rate of the prepared expanded graphite-based nickel-vanadium double-metal hydroxide composite material on fluorine ions can reach 96.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of expandable graphite. Background Art

[0002] The commonly used methods for preparing expandable graphite known at present mainly include chemical oxidation method and electrochemical method. The chemical oxidation method is easy to operate in preparing expandable graphite, can achieve large-scale production, and has relatively low production cost. However, it is easy to over-oxidize, the reaction is too violent, and it is difficult to accurately control the quality of the product. The product is mainly used in low-end fields. In addition, this method uses a large amount of oxidant, which seriously corrodes the equipment and pollutes the environment. The electrochemical method promotes the oxidation reaction of graphite by using metal materials as electrodes under a constant current to generate expandable graphite. This method avoids the use of a large amount of oxidants, reduces pollution to the environment, and improves production efficiency and product quality.

[0003] At present, the main factors restricting the application and promotion of expandable graphite are high cost, high sulfur content, poor oxidation resistance, etc. The present invention adopts fine-grained flake graphite (100 mesh-150 mesh), sulfur-free intercalation agent (such as perchloric acid, nitric acid, acetic acid, etc.), and electrochemical reactor. The oxidation time and oxidation intensity are controllable, and sulfur-free, low-cost, and expandable graphite with different expansion volumes can be obtained to meet the quality requirements of expandable graphite in different fields.

[0004] In addition, the invention further expands the application scope of the prepared fine-grained sulfur-free expandable graphite, and prepares it into an expandable graphite-based nickel-vanadium bimetallic hydroxide composite material, which is used to solve the problems of high cost, complex operation, low efficiency, secondary pollution, low adsorption capacity and poor treatment effect in the existing treatment of fluorine wastewater. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a preparation method and application of fine-grained sulfur-free expandable graphite.

[0006] A method for preparing fine-grained sulfur-free expandable graphite is specifically completed by the following steps:

[0007] 1. First, put the flake graphite powder into the mesh bag, and then fix the stainless steel plate in the middle of the mesh bag containing the flake graphite powder, so that the flake graphite powder on both sides of the stainless steel plate is even and symmetrical; use the stainless steel plate and flake graphite powder as anodes; place the anode in the reactor;

[0008] 2. Add electrolyte to the reactor, then put in a lead plate as the negative electrode, adjust the current density, and carry out electrolytic oxidation reaction for a period of time under stirring conditions;

[0009] 3. After the reaction is completed, the graphite is filtered by vacuum pressure, washed with water until neutral, and dried to obtain fine-grained sulfur-free expandable graphite;

[0010] The expansion ratio of the fine-grained sulfur-free expandable graphite described in step 3 is 160 mL / g to 220 mL / g.

[0011] A fine-grained sulfur-free expandable graphite is used to prepare an expanded graphite-based nickel-vanadium double metal hydroxide composite material.

[0012] The expanded graphite-based nickel-vanadium double metal hydroxide composite material is used to treat fluorine-containing wastewater, with an addition amount of 0.5 mg / L to 1.5 mg / L and an adsorption time of 2 h to 5 h at room temperature.

[0013] Advantages of the present invention:

[0014] 1. The present invention uses fine-grained flake graphite powder as raw material, adopts a sulfur-free intercalant (a mixture of perchloric acid and anhydrous acetic acid), uses an electrochemical reactor, fixes the position of the electrode plate, and adjusts the current density and oxidation reaction time to prepare sulfur-free, low-cost, expandable graphite with different expansion volumes; the sulfur-free intercalant used in the present invention can be used in a reaction, and after filtering, it is added to a newly configured electrolyte, which can save costs and a large amount of acid washing and treatment costs;

[0015] Second, the present invention can increase the current intensity and control the oxidation intensity by controlling the current density; and can control the intercalation time by adjusting the reaction time to obtain expandable graphite with different expansion volumes;

[0016] 3. The expanded graphite-based nickel-vanadium double metal hydroxide composite material prepared by the present invention can achieve a fluoride ion removal rate of 96.8%. DETAILED DESCRIPTION

[0017] Specific implementation method 1: This implementation method is a method for preparing fine-grained sulfur-free expandable graphite, which is characterized by being completed in the following steps:

[0018] 1. First, put the flake graphite powder into the mesh bag, and then fix the stainless steel plate in the middle of the mesh bag containing the flake graphite powder, so that the flake graphite powder on both sides of the stainless steel plate is even and symmetrical; use the stainless steel plate and flake graphite powder as anodes; place the anode in the reactor;

[0019] 2. Add electrolyte to the reactor, then put in a lead plate as the negative electrode, adjust the current density, and carry out electrolytic oxidation reaction for a period of time under stirring conditions;

[0020] 3. After the reaction is completed, the graphite is filtered by vacuum pressure, washed with water until neutral, and dried to obtain fine-grained sulfur-free expandable graphite;

[0021] The expansion ratio of the fine-grained sulfur-free expandable graphite described in step 3 is 160 mL / g to 220 mL / g.

[0022] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the particle size of the flake graphite powder in step 1 is 100-150 meshes; the reactor in step 1 is an enamel reactor. The other steps are the same as those in specific embodiment 1.

[0023] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the electrolyte described in step 2 is a mixture of perchloric acid and anhydrous acetic acid; the mass fraction of perchloric acid is 72%; the volume ratio of perchloric acid to anhydrous acetic acid in the electrolyte is (1-4):1; the mass ratio of the electrolyte described in step 2 to the flake graphite powder is 8:1. The other steps are the same as those in specific embodiment 1 or 2.

[0024] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that the current density described in step 2 is 0.04A / cm 2 ~0.08A / cm 2 The other steps are the same as those in Specific Embodiments 1 to 3.

[0025] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the time of the electrolytic oxidation reaction in step 2 is 0.5h to 1h; the stirring speed in step 2 is 100r / min to 200r / min, and the temperature during stirring is less than 40°C; the lead plate in step 2 is located at two-thirds of the reactor. The other steps are the same as those in specific embodiments 1 to 4.

[0026] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the drying temperature in step 3 is 60°C to 80°C, and the moisture content of the fine sulfur-free expandable graphite in step 3 is ≤3%. The other steps are the same as those in specific embodiments 1 to 5.

[0027] Specific embodiment seven: This embodiment is a fine-grained sulfur-free expandable graphite used to prepare an expanded graphite-based nickel-vanadium double metal hydroxide composite material.

[0028] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the preparation method of the expanded graphite-based nickel-vanadium double metal hydroxide composite material is specifically completed according to the following steps:

[0029] Dissolve nickel dichloride hexahydrate, vanadium trichloride and a surfactant in deionized water, then add urea and fine sulfur-free expandable graphite, and perform ultrasonic treatment for a period of time to obtain a mixed solution; transfer the mixed solution to a polytetrafluoroethylene autoclave for hydrothermal reaction, and then naturally cool to room temperature to obtain a reaction product; wash and dry the reaction product to obtain an expanded graphite-based nickel-vanadium double metal hydroxide composite material. The other steps are the same as those in the first to seventh embodiments.

[0030] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the surfactant is sodium dodecylbenzene sulfonate or sodium dodecyl sulfate; the molar ratio of vanadium trichloride, nickel dichloride hexahydrate and urea is 1:(2-4):1; the molar ratio of vanadium trichloride to surfactant is 1:2; the molar ratio of the total molar amount of nickel dichloride hexahydrate and vanadium trichloride to fine-grained sulfur-free expandable graphite is (5-8):1; the temperature of the hydrothermal reaction is 110°C to 120°C, the time of the hydrothermal reaction is 5h to 8h; the time of the ultrasound is 10min to 20min. The other steps are the same as those of specific embodiments 1 to 8.

[0031] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the expanded graphite-based nickel-vanadium double metal hydroxide composite material is used to treat fluorine-containing wastewater, the dosage is 0.5 mg / L to 1.5 mg / L, and the adsorption time at room temperature is 2h to 5h. The other steps are the same as those of specific embodiments 1 to 9.

[0032] The following examples are used to verify the beneficial effects of the present invention:

[0033] Embodiment 1: A method for preparing fine-grained sulfur-free expandable graphite is specifically completed by the following steps:

[0034] 1. First, put the flake graphite powder into the mesh bag, and then fix the stainless steel plate in the middle of the mesh bag containing the flake graphite powder, so that the flake graphite powder on both sides of the stainless steel plate is even and symmetrical; use the stainless steel plate and flake graphite powder as anodes; place the anode in the reactor;

[0035] The particle size of the flake graphite powder described in step 1 is 100 mesh;

[0036] The reactor described in step 1 is an enamel reactor;

[0037] 2. Add electrolyte to the reactor, put a lead plate into the electrolyte as a negative electrode, adjust the current density, and carry out electrolytic oxidation reaction for a period of time under stirring conditions;

[0038] The electrolyte described in step 2 is a mixture of perchloric acid and anhydrous acetic acid; wherein the mass fraction of perchloric acid is 72%; and the volume ratio of perchloric acid to anhydrous acetic acid in the electrolyte is 4:1;

[0039] The mass ratio of the electrolyte to the flake graphite powder described in step 2 is 8:1;

[0040] The current density described in step 2 is 0.06A / cm 2 ;

[0041] The electrolytic oxidation reaction time in step 2 is 45 min;

[0042] The stirring speed in step 2 is 160 r / min, and the temperature during stirring is less than 40° C.;

[0043] 3. After the reaction is completed, the graphite is filtered by vacuum pressure, washed with water until neutral, and dried to obtain fine-grained sulfur-free expandable graphite;

[0044] The drying temperature in step 3 is 80°C;

[0045] The expansion ratio of the fine-grained sulfur-free expandable graphite described in step 3 is 160 mL / g.

[0046] The moisture content of the fine-grained sulfur-free expandable graphite described in step 3 is ≤3%.

[0047] The method for preparing fine-grained sulfur-free expandable graphite in this embodiment uses fine-grained flake graphite as raw material. Compared with conventional methods, the electrolyte uses sulfur-free mixed acid, and the mixed acid can be reused, which reduces the amount of mixed acid used and greatly reduces costs. At the same time, the use of this method can reduce corrosion to equipment, avoid the use of large amounts of oxidants, and reduce pollution to the environment.

[0048] Embodiment 2: A method for preparing fine-grained sulfur-free expandable graphite is specifically completed by the following steps:

[0049] 1. First, put the flake graphite powder into the mesh bag, and then fix the stainless steel plate in the middle of the mesh bag containing the flake graphite powder, so that the flake graphite powder on both sides of the stainless steel plate is even and symmetrical; use the stainless steel plate and flake graphite powder as anodes; place the anode in the reactor;

[0050] The particle size of the flake graphite powder described in step 1 is 100 mesh;

[0051] The reactor described in step 1 is an enamel reactor;

[0052] 2. Add electrolyte to the reactor, put a lead plate into the electrolyte as a negative electrode, adjust the current density, and carry out electrolytic oxidation reaction for a period of time under stirring conditions;

[0053] The electrolyte described in step 2 is a mixture of perchloric acid and anhydrous acetic acid; wherein the mass fraction of perchloric acid is 72%; and the volume ratio of perchloric acid to anhydrous acetic acid in the electrolyte is 4:1;

[0054] The mass ratio of the electrolyte to the flake graphite powder described in step 2 is 8:1;

[0055] The current density described in step 2 is 0.06A / cm 2 ;

[0056] The electrolytic oxidation reaction time in step 2 is 60 min;

[0057] The stirring speed in step 2 is 160 r / min, and the temperature during stirring is less than 40° C.;

[0058] 3. After the reaction is completed, the graphite is filtered by vacuum pressure, washed with water until neutral, and dried to obtain fine-grained sulfur-free expandable graphite;

[0059] The drying temperature in step 3 is 80°C;

[0060] The expansion ratio of the fine-grained sulfur-free expandable graphite described in step 3 is 200 mL / g.

[0061] The moisture content of the fine-grained sulfur-free expandable graphite described in step 3 is ≤3%.

[0062] The method for preparing fine-grained sulfur-free expandable graphite in this embodiment can obtain sulfur-free, low-cost expandable graphite with an expansion ratio of 200 times by adjusting the reaction time and controlling the intercalation time, so as to meet the quality requirements of expandable graphite in different fields.

[0063] Application Example 1: A method for preparing an expanded graphite-based nickel-vanadium double metal hydroxide composite material using the fine-grained sulfur-free expandable graphite prepared in Example 2 is specifically completed in the following steps:

[0064] 1. Dissolve nickel dichloride hexahydrate, vanadium trichloride and a surfactant in deionized water, then add urea and fine-grained sulfur-free expandable graphite, and ultrasonicate for 15 minutes to obtain a mixed solution; transfer the mixed solution to a polytetrafluoroethylene autoclave for hydrothermal reaction, and then naturally cool to room temperature to obtain a reaction product; wash the reaction product with deionized water for 3 times, and then dry it at 80°C to obtain an expanded graphite-based nickel-vanadium double metal hydroxide composite material;

[0065] The surfactant is sodium dodecylbenzene sulfonate;

[0066] The molar ratio of vanadium trichloride, nickel dichloride hexahydrate and urea is 1:2:1;

[0067] The molar ratio of vanadium trichloride to surfactant is 1:2;

[0068] The molar ratio of the total molar amount of the nickel dichloride hexahydrate and the vanadium trichloride to the fine-grained sulfur-free expandable graphite is 8:1;

[0069] The temperature of the hydrothermal reaction is 110°C and the time of the hydrothermal reaction is 8h;

[0070] 2. Use sodium fluoride to prepare a 30 mg / L fluoride ion solution; add the expanded graphite-based nickel-vanadium double metal hydroxide composite material to the 30 mg / L fluoride ion solution for adsorption for 5 hours, pH = 7, the addition amount is 0.5 mg / L, and the fluoride ion removal rate is tested;

[0071] The results show that the removal rate of fluoride ions using the expanded graphite-based nickel-vanadium double metal hydroxide composite material prepared in Example 1 can reach 96.8%.

[0072] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing fine-grained sulfur-free expandable graphite, characterized in that The preparation method is specifically completed according to the following steps:

1. First, put the flake graphite powder into the mesh bag, and then fix the stainless steel plate in the middle of the mesh bag containing the flake graphite powder, so that the flake graphite powder on both sides of the stainless steel plate is even and symmetrical; use the stainless steel plate and flake graphite powder as anodes; place the anode in the reactor; 2. Add electrolyte to the reactor, then put in a lead plate as the negative electrode, adjust the current density, and carry out electrolytic oxidation reaction for a period of time under stirring conditions; 3. After the reaction is completed, the graphite is filtered by vacuum pressure, washed with water until neutral, and dried to obtain fine-grained sulfur-free expandable graphite; The expansion ratio of the fine-grained sulfur-free expandable graphite described in step 3 is 160 mL / g to 220 mL / g.

2. The method for preparing fine-grained sulfur-free expandable graphite according to claim 1, characterized in that The particle size of the flake graphite powder described in step one is 100 mesh to 150 mesh; the reactor described in step one is an enamel reactor.

3. The method for preparing fine-grained sulfur-free expandable graphite according to claim 1, characterized in that The electrolyte described in step 2 is a mixture of perchloric acid and anhydrous acetic acid; wherein the mass fraction of perchloric acid is 72%; the volume ratio of perchloric acid to anhydrous acetic acid in the electrolyte is (1-4):1; the mass ratio of the electrolyte described in step 2 to the flake graphite powder is 8:

1.

4. The method for preparing fine-grained sulfur-free expandable graphite according to claim 1, characterized in that The current density described in step 2 is 0.04A / cm 2 ~0.08A / cm 2 .

5. The method for preparing fine-grained sulfur-free expandable graphite according to claim 1, characterized in that The time of the electrolytic oxidation reaction in step 2 is 0.5h to 1h; the stirring speed in step 2 is 100r / min to 200r / min, and the temperature during stirring is less than 40°C; the lead plate in step 2 is located at two-thirds of the reactor.

6. The method for preparing fine-grained sulfur-free expandable graphite according to claim 1, characterized in that The drying temperature in step 3 is 60° C. to 80° C.; the moisture content of the fine-grained sulfur-free expandable graphite in step 3 is ≤3%.

7. Application of a fine-grained sulfur-free expandable graphite prepared by the preparation method according to claim 1, characterized in that A fine-grained sulfur-free expandable graphite is used to prepare an expanded graphite-based nickel-vanadium double metal hydroxide composite material.

8. The use of a fine-grained sulfur-free expandable graphite according to claim 7, characterized in that The preparation method of the expanded graphite-based nickel-vanadium double metal hydroxide composite material is specifically completed according to the following steps: Nickel dichloride hexahydrate, vanadium trichloride and a surfactant are dissolved in deionized water, and then urea and fine-grained sulfur-free expandable graphite are added, and ultrasonic treatment is performed for a period of time to obtain a mixed solution; the mixed solution is transferred to a polytetrafluoroethylene autoclave for hydrothermal reaction, and then naturally cooled to room temperature to obtain a reaction product; the reaction product is cleaned and dried to obtain an expanded graphite-based nickel-vanadium bimetallic hydroxide composite material.

9. The use of a fine-grained sulfur-free expandable graphite according to claim 8, characterized in that The surfactant is sodium dodecylbenzene sulfonate or sodium dodecyl sulfate; the molar ratio of the vanadium trichloride, nickel dichloride hexahydrate and urea is 1:(2-4):1; the molar ratio of the vanadium trichloride to the surfactant is 1:2; the molar ratio of the total molar amount of the nickel dichloride hexahydrate and vanadium trichloride to the fine-grained sulfur-free expandable graphite is (5-8):1; the temperature of the hydrothermal reaction is 110°C-120°C, the time of the hydrothermal reaction is 5h-8h; the time of the ultrasound is 10min-20min.

10. The use of a fine-grained sulfur-free expandable graphite according to claim 8, characterized in that The expanded graphite-based nickel-vanadium double metal hydroxide composite material is used to treat fluorine-containing wastewater, with an addition amount of 0.5 mg / L to 1.5 mg / L and an adsorption time of 2 h to 5 h at room temperature.